2020
DOI: 10.1088/2053-1591/abcdd9
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behavior of Inconel 625 deposited metal in molten KCl-MgCl2

Abstract: In order to investigate the corrosion behavior of Inconel 625 deposited metal in molten KCl and MgCl2, the corrosion behavior of deposited metal immersed in molten salt for 60 h at 700 °C and 900 °C was studied by static corrosion immersion method. X-ray diffraction (XRD) and Geminisem300 were used to systematically study the phase composition, corrosion morphology and element distribution of the deposited metal. The results show that: the corrosion weight loss of the deposited metal showed an increasing trend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…This argument is further supported by the fact that the OH − and O − signals detected by ToF-SIMS overlap with Mg − and Cl-signals corresponding to residual salt trapped within the pores. As noted, Cr 2 O 3 has been regularly cited by other investigators (Salinas-Solano et al, 2014;Zhu et al, 2016;Grégoire et al, 2020;Knosalla et al, 2020;Yang et al, 2020). In this investigation, intergranular Cr-O formation is an indicator of Cr 2 O 3 formation contributing to the propagation of the corrosion front.…”
Section: Transmission Electron Microscopysupporting
confidence: 62%
See 4 more Smart Citations
“…This argument is further supported by the fact that the OH − and O − signals detected by ToF-SIMS overlap with Mg − and Cl-signals corresponding to residual salt trapped within the pores. As noted, Cr 2 O 3 has been regularly cited by other investigators (Salinas-Solano et al, 2014;Zhu et al, 2016;Grégoire et al, 2020;Knosalla et al, 2020;Yang et al, 2020). In this investigation, intergranular Cr-O formation is an indicator of Cr 2 O 3 formation contributing to the propagation of the corrosion front.…”
Section: Transmission Electron Microscopysupporting
confidence: 62%
“…Furthermore, the Frontiers in Nuclear Engineering frontiersin.org discontinuous porous network observed in this study corresponds to intergranular attack, which has been observed in Alloy 617 over shorter time scales (Sun et al, 2018a). The dealloying of Cr in Alloy 617 due to molten salt corrosion is commonly attributed to the formation of corrosion products, specifically Cr 2 O 3 , from Cr reacting with oxidant impurities in the salt, such as water (Salinas-Solano et al, 2014;Zhu et al, 2016;Guo et al, 2018;Grégoire et al, 2020;Knosalla et al, 2020;Yang et al, 2020). Several mechanisms explaining the role of Cr in propagating the corrosion front have been proposed.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
See 3 more Smart Citations